2019
DOI: 10.1051/epjconf/201921201012
|View full text |Cite
|
Sign up to set email alerts
|

The Super C-τ Factory particle identification system options

Abstract: The Super C-τ (SCT) Factory at Novosibirsk is a project of new colliding beam experiment proposed in Budker Institute of Nuclear Physics. Electron-positron collider based on Crab-Waist technique for operation energy range 2–5 GeV in center of mass is suggested. The luminosity up to 1035cm−1s−1 (in 100 times higher than in operated today experiments in this energy region) is expected. To perform broad experimental program of the project successfully the excellent particle identification (PID) system is needed. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…It was shown that such system is able to provide good µ/πseparation from 0.5 to 0.9 GeV/c. More detailed description of the proposed system can be found in [28,29].…”
Section: Threshold Aerogel Cherenkov Counters Ashiph With Sipmmentioning
confidence: 99%
See 1 more Smart Citation
“…It was shown that such system is able to provide good µ/πseparation from 0.5 to 0.9 GeV/c. More detailed description of the proposed system can be found in [28,29].…”
Section: Threshold Aerogel Cherenkov Counters Ashiph With Sipmmentioning
confidence: 99%
“…Therefore the "ToF+ToP" technique with 30 ps intrinsic resolution were considered as additional PID subsystem which able to provide µ/π-separation in the low momentum range. Some details and conceptual design of the "ToF+ToP" system for the SCT detector based on quartz bars (5 × 5 × 250 mm 3 ) and 1648 multi-anode MCP-PMTs with rectangular shape 40 × 20 mm are given in [28,29]. It was shown with help of parametric simulation that such system is able to provide µ/π-separation at the level of better than 3σ up to momentum 0.7 GeV/c (see section 4).…”
Section: Dirc-like and Tof Optionsmentioning
confidence: 99%